AN ANALYSIS NON LIVING PERSONIFICATION IN NORTHLANE’S SELECTED SONGS - Genville Darmarris (TEKNOSASTIK, 2021)
This article is entitled "An Analysis of Non Living Personification in Northlane’s Selected Songs". This article aims to identify which lyrics are containing the Non living personification used in the selected songs of metal band Northlane and its meaning. The theory used is the theory from Zhu (1991) to identify which lyrics from selected songs such as : Free fall, Talking Heads, Eclipse, Vultures those are containing the Non living personification and theory meaning from Leech (1981). In this article, the method used in this research is the library method. The method used for presenting data is an informal method, which means that the data will be described qualitatively with the description method which includes several descriptions and support for formal methods, which means that in this article there is a table used to explain the classification of the data used. After analyzing the data, the writer concluded and found the result that in each songs such as : Free fall, Talking Heads, Eclipse, Vultures there are some lyrics that contain non living personification based from theory of personification by Zhu (1991), but there are only 5 types of meaning found from 7 types of meaning based on the theory of meaning by Leech (1981) that found from the data such as Conceptual, Connotative, Social, Affective And Thematic meaning.Keywords: Personification, Non Living Personification, lyrics, meaning